2016
DOI: 10.1016/j.sbi.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The thermostability and specificity of ancient proteins

Abstract: Were ancient proteins systematically different than modern proteins? The answer to this question is profoundly important, shaping how we understand the origins of protein biochemical, biophysical, and functional properties. Ancestral sequence reconstruction (ASR), a phylogenetic approach to infer the sequences of ancestral proteins, may reveal such trends. We discuss two proposed trends: a transition from higher to lower thermostability and a tendency for proteins to acquire higher specificity over time. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
106
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 54 publications
2
106
1
Order By: Relevance
“…In addition, such comparative studies are often limited by epistatic effects, which complicate the identification of sequence determinants and mechanisms (12, 13). More importantly, these extant homologs can reveal only the outcomes of an evolutionary process, and not the mechanism by which different properties arose from a common ancestral state (14).In contrast, ancestral sequence reconstruction (ASR) allows direct interrogation of a protein's history by using evolutionary relationships and sequences of modern homologs to statistically infer ancestral states within a family's phylogenetic tree (12)(13)(14). Characterizing these ancestral proteins will reveal trends in folding properties and also help identify the evolutionary demands on folding.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, such comparative studies are often limited by epistatic effects, which complicate the identification of sequence determinants and mechanisms (12, 13). More importantly, these extant homologs can reveal only the outcomes of an evolutionary process, and not the mechanism by which different properties arose from a common ancestral state (14).In contrast, ancestral sequence reconstruction (ASR) allows direct interrogation of a protein's history by using evolutionary relationships and sequences of modern homologs to statistically infer ancestral states within a family's phylogenetic tree (12)(13)(14). Characterizing these ancestral proteins will reveal trends in folding properties and also help identify the evolutionary demands on folding.…”
mentioning
confidence: 99%
“…This information then can be used to engineer proteins with desired folding properties. ASR has already provided important insights into evolutionary trends in stability, specificity, and other biophysical properties (12)(13)(14)(15)(16)(17)(18)(19)(20).Previously, we used ASR to study the thermostability of the ribonuclease H (RNase H) family and demonstrated divergent trends in thermostability along mesophilic and thermophilic lineages (16). Here we examined the folding mechanism and associated rates of these reconstructed ancestral RNases H. The folding pathway of the two extant homologs, Escherichia coli RNase H (ecRNH) and Thermus thermophilus RNase H Significance Because protein folding is crucial to proper cellular function, there must be evolutionary pressures on how a protein achieves and maintains its folded structure.…”
mentioning
confidence: 99%
See 3 more Smart Citations